A new icriodontid conodont cluster with specific mesowear supports an alternative apparatus motion model for Icriodontidae. (2nd September 2018) - Suttner, Thomas J.; Kido, Erika; Briguglio, Antonino
Abstract : Increasing numbers of conodont discoveries with soft tissue preservation, natural assemblages and fused clusters of the hard tissue have strengthened the hypothesis regarding the function and mechanism of the conodont feeding apparatus. Exceptional fossil preservation serves as a solid basis for modern reconstructions of the conodont apparatus illustrating the complex interplay of the single apparatus elements. Reliable published models concern the ozarkodinid apparatus of Pennsylvanian and Early Triassic conodonts. Recognition of microwear and mammal-like occlusion, especially of platform elements belonging to individuals of the genus Idiognathodus, allows rotational closure to be interpreted as the crushing mechanism of ozarkodinid platform (P1) elements. Here we describe a new icriodontid conodont cluster of Caudicriodus woschmidti that consists of one pair of icriodontan (I) and 10 pairs of coniform (C1–5) elements, with I elements being preserved in interlocking position. The special kind of element arrangement within the fused cluster provides new insights into icriodontid apparatus reconstruction and notation of elements. However, orientation of coniform elements is limited to a certain degree by possible preservational bias. Four possible apparatus models are introduced and discussed. Recognition of specific wear on denticle tips of one of the icriodontan elements forms the basis for an alternative hypothesis of apparatus motion. Analysis of tip wear suggests a horizontal, slightly elliptical motion of opposed, antagonistically operating I elements. This is supported by similar tip wear from much better preserved, but isolated, elements of Middle Devonian icriodontids. More detailed interpretation of the masticatory movement will allow enhanced understanding of anatomical specifications, diet and palaeobiology of different euconodont groups.